Analisis Peran Kepala Sekolah sebagai Supervisor dalam Meningkatkan Prestasi Belajar Pendidikan Agama Islam di Era Digitalisasi Peserta Didik SDIT Asy Syaamil Tahun Pelajaran 2023/2024 - Sari, Rosita; Ihsan, Muh.; Nasution, Yassir Arafat (NABAWI: Jurnal Penelitian Pendidikan Islam, 2024)
The digitalization era presents many challenges and new opportunities in Islamic Education, requiring school principals as supervisors to play an active role in leveraging digital technology by involving teachers to improve students' Islamic Education learning achievements. This study aims to analyze the role of the school principal as a supervisor, the utilization of digital technology in the learning process, and the impact of this role on improving students' learning achievements. The research approach used is descriptive qualitative with observation, interview, and documentation methods. The research subjects are the school principal, Islamic Education teachers, and students. The results of the study show the importance of the school principal's role as an active supervisor, providing guidance and support as well as teacher involvement in technology-based learning to create a learning environment that enhances students' Islamic Education achievements. The conclusion from the study results is that the active role of the school principal and the professionalism of teachers are crucial in ensuring that the use of digital technology positively impacts students' learning achievements. Improving Islamic Education learning achievements in the digitalization era can occur partly due to the active role of the school principal in providing technology, support and training for teachers, as well as supervision and evaluation.